Re-examination of son-preference based on attitude structure theory under the background of gender imbalance in China - Shang, Zijuan; Chi, Baihui; Liu, Ze (Frontiers in Psychology, 2023)
Introduction The gender imbalance in China has a long history, and the consequences have begun to emerge, threatening sustainable population development. Against the backdrop of a persistently high sex ratio at birth, the paper introduces the theory of attitude structure to construct an analytical framework explaining the influencing factors of son preference and re-examining the son preference culture. Methods Based on the micro-level data from Jiangxi, Guangxi, Guizhou, and Shaanxi Province, this paper adopts a binary logistics model to analyzes the impacts of three cognitive factors on son preference. Results The results show that surname inheritance, the utility of elderly care, and the social value in the boy utility evaluation are the main influencing factors in the preference for a son. Social gender assessment, perception of gender imbalance, personal income, education level, health status, and the number of existing children individually correlate with son preference. After comparing the two factors of boy utility evaluation and gender imbalance perception, it is discovered that after China enters a gender-imbalanced society, the perception of gender imbalance effectively reduces the preference for sons, and the son preference is the result of rational choice in people’s fertility process. Discussion Based on the above research, the paper proposes policy recommendations at both macro and micro levels from the standpoint of public governance.